In-silico activity prediction and docking studies of some 2, 9-disubstituted 8-phenylthio/phenylsulfinyl-9h-purine derivatives as Anti-proliferative agents - Ibrahim, Muhammad Tukur (Heliyon, 2020)
In-silico activity prediction was performed to predict new inhibitory activities of 2, 9-disubstituted 8-phenylthio/phenylsulfinyl-9h-purine derivatives as anti-proliferative agents using QSAR technique. The anti-proliferative agents were optimized using Density Functional Theory (DFT) method utilizing the B3LYP/6-31G* level of theory. Genetic Function Algorithm (GFA) was used to build the QSAR models. Out of the models built, the best one was selected and reported because of its fitness statistically with the following assessment parameters: R(2)(trng) = 0.919035, R(2)(adj) = 0.893733, Q(2)(cv) = 0.866475, R(2)(test) = 0.636217, and LOF = 0.215884. The selected model was further subjected to other assessment such as VIF, Y-scrambling test, applicability domain and found to be statistically significant. The binding mode of some selected 2, 9-disubstituted 8-phenylthio/phenylsulfinyl-9H-purine (ligands) in the active site of EGFR-tyrosine kinase (EGFR-TK) (receptor) was studied via Molecular docking. Molecule 22 was identified to have the highest binding energy (-10.4 kcal/mol) among the other selected ligands which it might be as a result of hydrogen interactions formed with MET793 (2.48599 Å, 2.04522 Å) & THR854 (3.76616 Å) amino acid residues and hydrophobic/other interactions with amino acid residues (LEU718, LEU844, MET766, VAL726, ALA743, LYS745 and MET790) in the active site of EGFR-tyrosine kinase (EGFR-TK). The drug-likeness of these selected anti-proliferative agents were predicted via the pharmacokinetics profile of the molecules utilizing SWISS ADME. The anti-proliferative agents were found to be orally safe by not having more than 1 violation of the Lipinski's rule of five. This research proposed a way for designing potent anti-proliferative agents against their target enzyme.